2020
DOI: 10.1002/alr.22688
|View full text |Cite
|
Sign up to set email alerts
|

Association of subjective olfactory dysfunction and 12‐item odor identification testing in ambulatory COVID‐19 patients

Abstract: Background Acute loss of smell and taste are well‐recognized symptoms of coronavirus disease 2019 (COVID‐19), yet the correlation between self‐reported and psychophysical olfactory function remains unclear. Understanding the reliability of self‐reported smell loss in ambulatory cases can assess the utility of this screening measure. Methods A prospective, longitudinal study evaluating patient‐reported and measured olfactory function using the validated 12‐item Brief Smell Identification Test (BSIT) was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 29 publications
3
36
2
1
Order By: Relevance
“…Our results show that objectively assessed smell function using UPSIT correlates well with perceived smell function in this population, which highlights the reliability of our subjective patient-reported data on smell function following COVID-19. This finding is in line with a study conducted in ambulatory COVID-19 patients using the 12-item Brief Smell Identification Test (BSIT) which also concluded that self-reported olfactory loss is a strong predictor of abnormal olfactory function [39]. Furthermore, this highlights that in this subsample, tested 21.6 ± 4.7 weeks since the onset of their symptoms, 20% of participants had ongoing loss of their sense of smell, who would meet diagnostic criteria for both long-COVID and chronic COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that objectively assessed smell function using UPSIT correlates well with perceived smell function in this population, which highlights the reliability of our subjective patient-reported data on smell function following COVID-19. This finding is in line with a study conducted in ambulatory COVID-19 patients using the 12-item Brief Smell Identification Test (BSIT) which also concluded that self-reported olfactory loss is a strong predictor of abnormal olfactory function [39]. Furthermore, this highlights that in this subsample, tested 21.6 ± 4.7 weeks since the onset of their symptoms, 20% of participants had ongoing loss of their sense of smell, who would meet diagnostic criteria for both long-COVID and chronic COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that objectively assessed smell function using UPSIT correlates well with perceived smell function in this population, which highlights the reliability of our subjective patient-reported data on smell function following COVID-19. This nding is in line with a study conducted in ambulatory COVID-19 patients using the 12-item Brief Smell Identi cation Test (BSIT) which also concluded that self-reported olfactory loss is a strong predictor of abnormal olfactory function [38]. Furthermore, this highlights that in this subsample, tested 21.6 ±4.7 weeks since the onset of their symptoms, 20% of participants had ongoing loss of their sense of smell, who would meet diagnostic criteria for both long-COVID and chronic COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of olfactory dysfunction has varied widely between 15% and 96% based on self‐reported and quantitatively measured data 115–117 . The ability to accurately recognize one's olfactory impairment is debated, 115,2476–2479 but self‐reported olfactory assessment is valuable for initial screenings when psychophysical testing cannot be conducted 2476 . Clinical implications of olfactory dysfunction as a prognostic marker for the disease also remain controversial 2480–2484 .…”
Section: Crs Management In the Context Of Covid‐19mentioning
confidence: 99%